Physiology Response and Resistance Evaluation of Twenty Coconut Germplasm Resources under Low Temperature Stress - Chengxu Sun; Ruining Zhang; Zhouyu Yuan; Hongxing Cao; Jerome Jeyakumar John Martin (Horticulturae, 2021)
Coconut (Cocos nucifera L.) is a tropical evergreen crop with high economic value. Low temperature is one of the main environmental factors that limit coconut productivity. Therefore, it is necessary and significant to research the growth trend and physiological changes of coconuts under a low temperature environment. In this study, the physiological response of 20 coconut germplasm resources is presented in an integrated perspective to provide a holistic view of the behavior of coconut trees facing cold stress under four temperature conditions (25 °C, 15 °C, 10 °C, 5 °C). It was shown that low temperature would lead to the increase of relative electrical conductivity, MDA content, soluble protein content, and proline content. In addition, the activities of defense enzymes (SOD, POD, CAT, APX) were increased to resist the cold environment. In a comprehensive analysis, it was revealed that coconut germplasms with high cold resistance, such as C2, C7, and C10 as well as POD activity, proline content, and soluble protein content, were defined as representatives for coconut cold resistance evaluation. Through the exploration of osmotic adjustment substances and defense enzymes, the breeding and quality improvement of cold-resistant coconut varieties could be promoted. As a result, understanding the physiological response and tolerance mechanisms of coconuts to low temperature stress was essential, as this perception may serve as the foundation for coconut resistance evaluation, cultivation, and breeding.